Rural Development through Digital India Initiative - Usha Rani (International Journal on Economics, Finance and Sustainable Development, 2021)
Various initiatives in the recent past portrayed the significant role that the I.C.T plays in the realm of rural development. Several projects have reduced the costs, and it also has increased transparency. A large number of rural e-Governance applications, developed as pilot projects were aimed at offering easy access to citizen services and improved processing of government to citizen transactions. The world has transformed from knowledge savvy to techno knowledge savvy. The things should be available on one click. The Digital India programme comprises of various initiatives each targeted to prepare India for becoming a knowledge economy and for bringing good governance to citizens through synchronized and coordinated engagement of the entire government. Digital indicates to electronic technology which generates stores and processes data. It is stored in a virtual central repository that can be accessed anytime, anywhere, through established protocols. Digital Technologies include Cloud Computing and Mobile Applications. Digital India is one of the steps by the government to motivate and connect Indian Economy to a knowledge savvy world. The overall programme is focused to develop India for a knowledgeable future by developing central technology for allowing revolution which covers many departments under one umbrella programme .The main objective of this research paper is to study the positive impact that Digitization of Indian economy will have on the growth and development of Rural Indian Sector.